Deux siècles de musique à Versailles = Two centuries of music at Versailles - Pluhar, Christina 1965-; Gens, Véronique 1966-; Rousset, Christophe 1961-; Leonhardt, Gustav 1928-2012; Niquet, Hervé 1957- (Vox Lucida, 2011)
"The Chateau de Versailles is bustling with excitement. From the Orangerie to the restored hall of Mirror, from the Grand Stables to the King's apartments, music is going to take over the Chateau. For you, musicians of today will bring to life music from the time of Louis XIV, Louis XV and Louis XVI. So let's open the doors and take a trip through two centuries of music at the Chateau de Versailles"--Container
Originally produced in 2008 (c2007 on container). - Program notes in French and English (6 p. : col. ill.) inserted in container. - ARTE France & Camera Lucida Productions present ; the Château de Versailles and the Centre de Musique Baroque de Versailles present. - Concerts recorded in the Château de Versailles, 2008. - DVD ; NTSC.
Christina Pluhar ; Veronique Gens ; Christophe Rousset ; Gustav Leonhardt ; Herve Niquet ; Stephanie d'Oustrac ; Roberta Invernizzi ; Louis Langree ; Lionel Renoux ; Les Talens Lyriques ; Le Concert Spirituel ; Concerto Koeln ; Ensemble Philidor ; Musica Florea ; Les Folies françoises ; Collegium vocale de Gand ; Ricercar Consort
Written & directed by Olivier Simonnet ; executive producer, François Bertrand
The reign of music -- Louis Xiv and Lully -- A new wave of composers -- A daily music -- Louis XV -- Rameau -- Louis xvi and the Italian composers -- Paris, heart of Europe -- End of reign
Passacaille /? Stefano Landi -- Musique hautbois / Artiste inconnu -- Amadis - Toi qui das ce tombeau / Lully -- Amadis - Ciel! O Ciel! / Lully -- Messe des Morts / Charpentier -- Le Carnaval de Venise - Mes yeux fermez vous a jamais / Campra -- 4eme Concert Royal - Folane / Couperin -- Basse de trompette / Marchand -- In Convertendo / Rameau -- Callirhoe - O nuit temoin de mes soupirs secrets / Destouches -- Les fetes d'Hebe - Tambourin / Rameau -- Ouverture en Fa Majeur / Duphly -- Sonate en Re Majeur / Mozart -- Hippolyte et Aricie - Prelude / Rameau -- Hippolyte et Aricie - Quels doux concerts / Rameau -- Castor et Pollux - Ouverture / Rameau -- Castor et Pollux - Tristes Apprets / Rameau -- Didone Abbandonata - Soy Regina / Piccini -- La Poule / Haydn -- Iphigenie en Aulide Dieux Puissants - Gluck -- Armide - Venez, Secondez mes desirs /? Gluck -- Quatuor en Sol Mineur / Cambini -- Caprice no. 2 / Gallay -- Passacaille / Stefano Landi
Keywords: Louis / XIV / King of France / Palaces / France / Versailles / History; Lully, Jean-Baptiste / 1632-1687; Rameau, Jean-Philippe / 1683-1764; Château de Versailles (Versailles, France) / History; Geschichte 1700-1800; Geschichte 1600-1700; Music / France / 17th century / History and criticism; Music / France / 18th century / History and criticism; Composers / France; Music and aristocracy / France; Geschichte; Musik; France / History / Bourbons, 1589-1789; Frankreich; Film; DVD-Video